Electrochemical cyclizations of organic halides catalyzed by electrogenerated nickel(I) complexes: towards environmentally friendly methodologies - Duñach, E. (2017)
This review concentrates on the intramolecular cyclizations of organic halides catalyzed by nickel complexes using an electrochemical methodology, as an alternative to the classical radical or transitionmetal catalyzed or mediated processes.